Anthelmintic efficacy of gold nanoparticles derived from a phytopathogenic fungus, Nigrospora oryzae. - Pradip Kumar Kar (Public Library of Science (PLoS), 2014)
Exploring a green chemistry approach, this study brings to the fore, the anthelmintic efficacy of gold nanoparticles, highlighting the plausible usage of myconanotechnology. Gold nanoparticles of ∼6 to ∼18 nm diameter were synthesized by treating the mycelia-free culture filtrate of the phytopathogenic fungus with gold chloride. Their size and morphology were confirmed by UV-Vis spectroscopy, DLS data, AFM and TEM images. The XRD studies reveal a crystalline nature of the nanoparticles, which are in cubic phase. The FTIR spectroscopic studies before and after the formation of nanoparticles show the presence of possible functional groups responsible for the bio-reduction and capping of the synthesized gold nanoparticles. The latter were tested as vermifugal agents against a model cestode Raillietina sp., an intestinal parasite of domestic fowl. Further, ultrastructural and biochemical parameters were used to corroborate the efficacy study.